2017
DOI: 10.1371/journal.pone.0177741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a strategy for enrolling the families of critically ill patients in research using limited human resources

Abstract: RationaleClinical trials of interventions aimed at the families of intensive care unit (ICU) patients have proliferated but recruitment for these trials can be challenging.ObjectivesTo evaluate a strategy for recruiting families of patients currently being treated in an ICU using limited human resources and time-varying daily screening over 7 consecutive daysMethodsWe screened the Johns Hopkins Hospital medical ICU census 7 days per week to identify eligible family members. We then made daily, in-person attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 48 publications
(48 reference statements)
0
39
0
Order By: Relevance
“…In recruitment, subjects were approached in the ICU. These surrogate decision makers present visiting their family member may be different from those who are not present (46). Our hypothetical clinical vignette methodology does not fully replicate the circumstances and emotional responses that arise in an actual clinician-family encounter.…”
Section: Discussionmentioning
confidence: 99%
“…In recruitment, subjects were approached in the ICU. These surrogate decision makers present visiting their family member may be different from those who are not present (46). Our hypothetical clinical vignette methodology does not fully replicate the circumstances and emotional responses that arise in an actual clinician-family encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the 111 patients (4%) had a legal document naming a healthcare agent in their medical chart. [15] Analyses regarding the external validity of this study sample have been previously reported. [15]…”
Section: Resultsmentioning
confidence: 99%
“…[15] Analyses regarding the external validity of this study sample have been previously reported. [15]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of this recruitment strategy have been previously published. [ 37 ] In this paper we refer to these people as proxies to encompass both healthcare agents and healthcare surrogates who have distinct legal definitions under Maryland state law. [ 38 , 39 ] If the family member initially enrolled was not the patient’s legal healthcare proxy, additional attempts were made to also enroll a legal proxy.…”
Section: Methodsmentioning
confidence: 99%